Kwestia dopuszczalności stosowania środków zabezpieczających w stosunku do nieletnich sprawców czynów karalnych. Część II - Góralski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article discusses the admissibility of precautionary measures against juvenile criminals. It refers to both juvenile offenders charged as adults pursuant to Art. 10 § 2 of the Criminal Code and 15–16-year-old offenders charged pursuant to the provisions of the Procedures in Legal Actions against Juveniles Act of 1982. The article presents the legal status concerning this issue in the period from 1997 to 2015 and relevant changes in the legal regulations concerning precautionary measures introduced by the amendment of the Criminal Code of 20th February 2015.A thesis formulated in the paper discussed here is that only one type of precautionary measure, which is confiscation, may be used against juveniles subject to the regulations of the Procedures in Legal Actions against Juveniles Act. In relation to juveniles charged under the Criminal Code only the precautionary measures which do not interfere with the provisions of Article 3 of the Criminal Code providing for the rule of humanitarian use of criminal penalties should be implemented. It refers mainly to these forms of isolation precautionary measures which would apply to juvenile criminals after serving imprisonment.
Keywords: środki zapobiegawcze; odpowiedzialność karna młodocianych przestępców; młodociani przestępcy; środki edukacyjne i naprawcze; areszt dla nieletnich